The Rainmaker and Other Stories - Ekwensi, Cyprian (Nigeria, 1965)
The other day I came across a little boy who could make the rain fall when he wanted.These opening words carry the reader into this collection of stories.
Keywords: Adventure; Juvenile Fiction; Short Stories